THE ROLE OF MACROPHAGES IN DAMAGE RECOVERY OF CENTRAL NERVOUS SYSTEM: NEW OPTIONS FOR TREATMENT OF NEUROLOGICAL DISORDERS - E. R. Chernykh; E. Ya. Shevela; A. A. Ostanin (Медицинская иммунология)
Evolution of existing paradigms on regenerative capacity of the central nervous system (CNS) and eventual role of immune cells in restoration of damaged nervous tissue offers new prospectives in treatment of neurological disorders based on immunotherapeutic approaches. Present review article addresses a role of macrophages in restoration of damaged CNS and provides data on functional heterogeneity of resident tissue macrophages (microglia), and monocyte-derived macrophages. We discuss possible ways of monocyte recruitment to CNS, relationships between microglia and recruited macrophages, as well as M1/M2 balance in neurological conditions. Moreover, the review proposes an experimental rationale for macrophage engagement into the CNS damage reconstruction, and concerns the mechanisms of macrophage regenerative activity. In summary, the data presented here allow us to suggest macrophages as a novel therapeutic target for suppression of neuroinflammation and enhancement of reparative processes. The first steps in the field are encouraging, with respect to clinical application of monocytes/macrophages or M1→M2 switching technologies for treatment of the neurological disorders, thus presuming a need for further research in this direction.